ANALISA PERBANDINGAN FUZZY LOGIC METODE TSUKAMOTO, SUGENO, MAMDANI DALAM PENENTUAN KELUARGA MISKIN - Sutara, Beben; Kuswanto, Heri (Infotekmesin, 2019)
The application of the Fuzzy Tsukamoto, Sugeno, and Mamdani methods in determining poor families in Sumedang Regency can be done by the three methods using poor family outcomes which differ from the results of all data calculations. From all data calculated using the fuzzy logic method of the Tsukamoto, Sugeno, and Mamdani methods, it can be concluded that there are 4 data classified as poor and 16 data classified as not poor in the Tsukamoto method, 8 data classified as poor and 12 data classified not poor in the Sugeno method, and 10 data classified as poor and 10 classified as not poor in the Mamdani method. These results indicate that each method has different results even though the input used is the same.